Web-server for discovering DNA motifs associated with genome instability - Lee, Yew Ti. (2012)
Meiotic recombination is an important biological research field which could identify inheritable genetic disease. Recent works have developed a new tool named “LDSplit”, which can provide a greater degree of assistance then previous technologies in this research field.